Adakah ‘Target Panic’ menyebabkan prestasi merudum di kalangan pemanah? / Mohamad Azmi Nias Ahmad ... [et al.] - Nias Ahmad, Mohamad Azmi; Ronny Linoby, Adam Feizrel Linoby; Kamaruzzaman, Kamarul Hisyam; Abd Jalil, Mohammad Zaamzamir (Universiti Teknologi MARA Cawangan Pulau Pinang, 2014)
‘Target Panic’ can make an archer to experience a disruption in their archery routines and techniques. The study is to explore the problem of ‘Target Panic’ among 28 archers who have experienced this emerging problem before. The objective of this study is to understand this issue better, to look into the differences of scores before and while an arher who is experiencing the 'Target Panic' and listing the recovery steps through the feedback received. Using primary data, 104 questionnaires were distributed and only 53 questionnaires were completed and returned. The instrument is then analyzed using Statistical Package for Social Science (SPSS) version 20.0 for t-test (two-tailed) comparison of scores before and during archers experiencing ‘Target panic’.Results show that there are significant differences in scores for the compound archers but no significant scores differences were found among recurver archers.